Pengaruh Level Penggunaan Jamur Mikoriza Terhadap Komposisi Nutrisi Hijauan Sorgum Sebagai Pakan - Alfonsius Minu Mali (Politeknik Negeri Jember, 2017)
The study aimed to evaluate the nutrient composition of sorghum forage with the addition of vesicular-arbuscular mycorrhizal fungi (VAM) was conducted for 5 months from June to November 2016. Sorghum is grown in polybags and placed on the forage land of the State Agricultural Polytechnic of Kupang. This study was conducted using a completely randomized design with 4 treatments and 5 replications, The treatment were: without mycorrhizal fungi (S0), mycorrhizal fungi 5 gram/polybag (S5), mycorrhizal fungus 10 gram/polybag (S10) and mycorrhizal fungus 15 gram/polybag. The measured variables were dry matter (DM) content, ash content, crude protein (CP) content, ether extract (EE) content, crude fiber (CF) content and nitrogen free ekstract (NFE) content. The data were analyzed by analysis of variance and followed by Duncan's multiple-range test. The results showed that the level of mycorrhizal fungi use only significant (P<0.05) to the ether extract (EE) content, crude fiber (CF) content and nitrogen free ekstract (NFE) content, while the content of dry matter (DM), ash content and crude protein (CP) content No significant effect (P> 0.05). The Average dry matter content 16,27%; ash content of 11.03%; crude protein content of 10.12%; ether extract content 2.94%; crude fiber content 22.61% and NFE content 53.30%. Keywords : sorghum forage, vesicular-arbuscular mycorrhizal (VAM) level, nutrient composition.